2021
DOI: 10.1155/2021/8267776
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between Serum LP-PLA2 and sST2 Levels and the Condition of Patients with Acute Heart Failure and Their Prognostic Value

Abstract: Acute heart failure (AHF) occurs mostly in the elderly, which is a syndrome that occurs in the later stages of the development of cardiovascular disease. Due to the sharp decline in the patient’s heart function, the patient has a high mortality rate and a poor prognosis, which seriously threaten the life safety of the elderly. Therefore, early diagnosis of AHF and timely treatment are extremely important. Lipoprotein-associated phospholipase A2 (LP-PLA2) is a newly discovered cardiovascular-specific inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Soluble ST2 (sST2) acts as a decoy receptor, directly bound to IL-33, and suppresses activation of JNK (c-Jun N-terminal kinase), NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) and ERK (extracellular signalregulated kinases), reversing the beneficial effects of the IL-33/ST2 system, thus destabilizing the defense mechanism. The association between sST2 and mortality rates was confirmed in patients with acute [10][11][12][13], chronic decompensated [14] and chronic HF [3,15,16]. Moreover, the association was observed regardless of the left ventricular ejection fraction (LVEF) values, as well as in patients with reduced ejection fraction (HFrEF) [3,17,18].…”
Section: Introductionmentioning
confidence: 73%
“…Soluble ST2 (sST2) acts as a decoy receptor, directly bound to IL-33, and suppresses activation of JNK (c-Jun N-terminal kinase), NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) and ERK (extracellular signalregulated kinases), reversing the beneficial effects of the IL-33/ST2 system, thus destabilizing the defense mechanism. The association between sST2 and mortality rates was confirmed in patients with acute [10][11][12][13], chronic decompensated [14] and chronic HF [3,15,16]. Moreover, the association was observed regardless of the left ventricular ejection fraction (LVEF) values, as well as in patients with reduced ejection fraction (HFrEF) [3,17,18].…”
Section: Introductionmentioning
confidence: 73%
“…In recent years, studies on the use of sST2 protein as a biomarker in acute and chronic HF have been published. In recent years, studies have been published on the usefulness of the sST2 as a biomarker in acute [9] and chronic decompensated HF [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%